2000
DOI: 10.1007/s002490000090
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of cell membrane ion channel activation by applied magnetic fields

Abstract: This letter re-examines a recently published calculation of the forces exerted on a membrane ion channel by a cation passing through in the presence of an externally applied magnetic field. We show here, in contradiction to the originally published calculation, that the forces generated due to the Lorentz force of the magnetic field on the cation are negligible compared with the forces required to activate an ion channel protein conformation change associated with the gating of the channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…It has been estimated that the force to mechanically open an ion channel is approximately 0.2–0.4 pN 33 . Therefore, we measured the force from magnetic treatment on the cells using a method described by Kim et al Briefly, iron-loaded, ferritin-expressing cells were fixed in paraformaldehyde, added to aqueous buffer and subjected to a static magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…It has been estimated that the force to mechanically open an ion channel is approximately 0.2–0.4 pN 33 . Therefore, we measured the force from magnetic treatment on the cells using a method described by Kim et al Briefly, iron-loaded, ferritin-expressing cells were fixed in paraformaldehyde, added to aqueous buffer and subjected to a static magnetic field.…”
Section: Methodsmentioning
confidence: 99%
“…These effects, combined with the exceptional simplicity of tSMS hardware, confer potential for therapeutic applications in psychiatry and neurology (15,16). 1 The mechanism for the effects of static magnetic fields on neural tissue remains unknown, although various possibilities have been discussed, including deformation of ion channels due to reorientation of diamagnetic anisotropic plasma membrane phospholipids (19), coupling of mechanically-activated ion channels to ferromagnetic particles (20), and activation of voltage-gated channels by the Hall effect (21,22). Nevertheless, both theoretical considerations and experimental results indicate that the magnetic dose (i.e., the characteristics of the magnetic flux density, or B-field) has a significant impact on response (1,10).…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that the increase in systolic BP may be a compensatory physiological response to the magnetohydrodynamic slowing of blood flow in an 8 T SMF [79]. Theoretical calculations have demonstrated that the SMF strength below 10 T cannot be a direct effect of Lorentz forces acting on the induced currents in the blood vessels [112] and calcium ions [113]. However, numerical evaluation of the fields raises safety concerns that body movements in a high SMF gradient may be able to induce electric currents in tissues which could be potentially harmful [114].…”
Section: Strong Intensity Fieldsmentioning
confidence: 90%